Pengaruh Profitabilitas, Keputusan Investasi, Dan Keputusan Pendanaan Terhadap Nilai Perusahaan Pada Perusahaan Pertambangan Sub Sektor Minyak Dan Gas Bumi Yang Terdaftar Di BEI Periode 2017-2021 - Febryana Sudarmaka Putri; Nur Rahmanti Ratih; Miladiah Kusumaningarti (Jurnal Akuntan Publik, 2025)
The purpose of this study is to determine partially or simultaneously with the variable profitability (which is proxied by ROE), investment decisions (which are proxied by PER), and funding decisions (which are proxied by DER) on firm value (which is proxied by PBV). The population in this study are mining companies in the oil and gas sub-sector which are listed on the Indonesia Stock Exchange for the 2017-2021 period either partially or simultaneously. The sampling technique uses saturated sampling method. From this method, all companies became the research sample during the five-year observation period. The total sample is 11 companies. The analytical method in this test uses multiple regression analysis using the SPSS version 25 test tool. The results show that partially profitability (which is proxied by ROE) has no effect on firm value (which is proxied by PBV, investment decisions (which are proxied by PER) has partially affected on firm value (which is proxied by PBV), and funding decisions (which are proxied by DER) partially have no effect on firm value (which is proxied by PBV), Profitability (which is proxied by ROE), investment decisions (which are proxied by PER), and funding decisions (which are proxied by DER) simultaneously affect firm value (which is proxied by PBV). The Fcount value is greater than the Ftable value (7.338>2.00758) with a significant value of 0.000 which means less than 0.05.